2019
DOI: 10.1186/s40644-019-0267-8
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of CT-guided percutaneous radiofrequency ablation for stage I thymoma

Abstract: BackgroundThymoma is a rare tumor that originates from thymic epithelial cells and is usually associated with myasthenia gravis. Radiofrequency ablation (RFA) is a minimally invasive and curative treatment for other tumors, but RFA has not been used for the early treatment of thymoma.MethodsThe current study included 13 patients with stage I thymoma who were not candidates for surgical resection or video-assisted thoracoscopic surgery (VATS). All patients underwent first-line CT-guided percutaneous RFA. The fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Other forms of treatment might be undertaken in patients with contraindications to surgical resection. While radiofrequency ablation has been shown to be effective in controlling disease in early stage thymomas [79], No data is available for use of this modality in NETTs. Moreover, for those patients in whom their NETTs are associated with Cushing's syndrome due to ectopic adrenocorticotropic hormone production, symptoms may be controlled with somatostatin analogues [7].…”
Section: Other Treatmentsmentioning
confidence: 99%
“…Other forms of treatment might be undertaken in patients with contraindications to surgical resection. While radiofrequency ablation has been shown to be effective in controlling disease in early stage thymomas [79], No data is available for use of this modality in NETTs. Moreover, for those patients in whom their NETTs are associated with Cushing's syndrome due to ectopic adrenocorticotropic hormone production, symptoms may be controlled with somatostatin analogues [7].…”
Section: Other Treatmentsmentioning
confidence: 99%
“…CT-guided RFA is an effective and safe method to manage osteoid osteoma, and the benefits can persist for a long time (Lassalle et al, 2017). In addition, CT-guided RFA has also been recommended in the treatment of stage I thymoma, which has few complications and minor trauma as well as good treatment outcomes (Dong et al, 2019). However, very little is understood regarding the role and mechanism of CT-guided RFA in CC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is generally considered an effective treatment method ( 16 , 17 ); however, some researchers have pointed out that for some patients with thymoma, surgical treatment may not be the best treatment method ( 18 ). It has been reported that for patients with stage I thymoma according to the Masaoka-Koga staging, open surgical resection carries the risk of potential surgical damage and other complications, and CT-guided percutaneous radiofrequency treatment of stage I thymoma is related to minor trauma, fewer complications, and good treatment results ( 19 ). In patients with Masaoka-Koga stage I and II thymoma, after appropriate surgical resection, auxiliary radiation treatment has no obvious effect on outcomes ( 20 ).…”
Section: Introductionmentioning
confidence: 99%